EPIDEMIOLOGICAL ASPECTS OF ALLERGIC CONJUNCTIVITIS: A CROSS SECTIONAL STUDY - Ayisha Kausar; Nadia Akhtar; Nighat Akbar (Journal of Ayub Medical College Abbottabad, 2022)
Background: Allergic conjunctivitis is a common ocular disease which not only affects vision but can also compromise the quality of life of patients to a greater extent. If it is not properly managed it can lead to decreased vision due to corneal complications. This study was conducted to evaluate the epidemiological aspects of allergic conjunctivitis. Methods: This cross-sectional study was carried out in the Ophthalmology department of Federal General Hospital, from June 2018 to June 2020. We enrolled 236 patients of allergic conjunctivitis. Data collection form consisted of a structured questionnaire, records of ocular findings using slit lamp biomicroscope and skin prick test results. Data analysis was done using SPSS version 23.0. Results: The mean age (±SD) of study population was 22.71±13.11 years, 60.2% were females. Most common type of conjunctivitis was vernal keratoconjunctivitis (VKC) 46.2%, followed by perennial (27.1%), seasonal (17.4%) and atopic (9.3%). There was significant association of type of conjunctivitis with the age, p-value<0.001. VKC was prevalent in patients of age <20 years. There was a significant association of gender with type of conjunctivitis, p-value =0.000. Perennial variety was more prevalent in females while VKC was common in males. Collateral atopy was present in 52.1% patients. Corneal involvement was seen in 17.8% patients. There was a significant association between corneal involvement and interference with daily visual activities, p-value 0.034. SPT was positive in 79.7% patients. Conclusion: Ocular allergies/ conjunctivitis was more prevalent in female population. VKC is the most common type of allergic conjunctivitis, prevalent in males of age <20 yrs. Allergic rhinitis was the most common co-morbidity followed by dermatitis.